Noninvasive assessment of congestive hepatopathy in patients with constrictive pericardial physiology using MR relaxometry. (1st September 2021) - Bogaert, Jan; Dresselaers, Tom; Imazio, Massimo; Sinnaeve, Peter; Tassetti, Luigi; Masci, Pier Giorgio; Symons, Rolf
Abstract: Background: Constrictive pericarditis represents a treatable cause of mainly right heart failure (RHF), characterized by increased filling pressures and congestive hepatopathy. We hypothesized assessment of T1 and T2 liver relaxation times enables to depict liver congestion, and thus to diagnose RHF. Methods: Cardiovascular magnetic resonance imaging (CMR) was performed in 45 pericarditis patients i.e., 25 with constrictive physiology (CP+), 20 with normal physiology (CP-), and 30 control subjects. CMR included morphologic and functional assessment of the heart and pericardium. Liver relaxation times were measured on T1 and T2 cardiac maps. Results: CP+ and CP- patients were predominantly male, but CP+ patients were on average 13 years older than CP- patients ( p = 0.003). T1 and T2 Liver values were significantly higher in CP+ than in CP- patients and controls, i.e. T1: 765 ± 102 ms vs 581 ± 56 ms and 537 ± 30 ms (both p < 0.001); T2: 63 ± 13 ms vs 50 ± 4 ms and 46 ± 4 ms (both p < 0.001). Extracellular volume (ECV) liver values were also increased, i.e. 42 ± 7% CP+ vs 31 ± 3% CP- and 30 ± 3% control (both p < 0.001). Using a cut-off right atrial pressure of >5 mmHg to discriminate between normal and increased pressure, native T1 liver yielded the highest AUC (0.926) at ROC analysis with a sensitivity of 79.3% and specificity of 95.6%. Gamma-glutamyl transpeptidase correlated well withT1 liver (r 2 = 0.43) and ECV liver (r 2 = 0.30). Excellent intra- and inter-reader agreement was found for T1, T2 and ECV measurement of the liver. Conclusions: Assessment of liver relaxation times in pericarditis patients provide valuable information on the presence of concomitant congestive hepatopathy, reflecting RHF. Highlights: Constrictive physiology in pericarditis patients represents a rare but potentially treatable cause of right heart failure Increased filling pressures in right heart failure cause liver congestion, eventually evolving towards liver cirrhosis In constrictive pericarditis patients, measurement of liver relaxation times may depict passive liver congestion, reflecting right heart failure.